Low preoperative adiponectin levels are associated with postoperative systemic inflammatory response following major colorectal cancer surgery - Sonja Škiljić; Ines Šahinović; Gordana Kristek; Hrvoje Vinković; Ivana Haršanji-Drenjančević; Dino Budrovac; Bojan Trogrlić; Josip Kocur; Nenad Nešković; Slavica Kvolik (Intensive Care Medicine Experimental, 2026)
Abstract Background Adiponectin is an adipokine secreted by adipose tissue that plays an important role in colorectal oncogenesis and the response to surgical stress through its anti-inflammatory effects. However, it remains unclear whether perioperative alterations in circulating adiponectin in patients undergoing colorectal cancer surgery are associated with early postoperative systemic inflammation. The aim of this study was to investigate the predictive value of perioperative adiponectin levels, interleukin-6 (IL-6), and standard inflammatory blood biomarkers for the development of postoperative systemic inflammatory response syndrome (SIRS) and complications following colorectal cancer surgery. Methods This prospective observational study included 57 patients scheduled for open colorectal cancer surgery. Blood samples for determination of white blood cell count (WBC), differential leukocyte count, C-reactive protein (CRP), adiponectin, and IL-6 were collected preoperatively and at 24 and 72 h after surgery. The occurrence of surgical and non-surgical postoperative complications until hospital discharge was recorded. Patients were divided into two groups according to the presence of clinical and laboratory signs of SIRS within 72 h after surgery. Results No statistically significant differences in demographic and clinical characteristics were observed between the SIRS and non-SIRS groups of patients. Patients who developed SIRS within 72 h after surgery had lower preoperative adiponectin levels, 10.1 (5.3–15.1) vs. 14.7 (9.6–20.9) mg/L, p = 0.02, and higher WBC, CRP, and CRP/albumin ratio. Multivariate logistic regression showed that among preoperative biomarkers, adiponectin was the only biomarker independently associated with postoperative SIRS, OR 0.91 (95% CI 0.83–0.99), p = 0.03. Using a cut-off serum level of preoperative adiponectin ≤ 7.5 mg/L, ROC analysis demonstrated sensitivity of 38.7% and specificity of 92.3% for predicting postoperative SIRS, with an AUC 0.673 (95% CI 0.534–0.812), p = 0.01. IL-6 measured 72 h after surgery demonstrated the highest predictive value for postoperative complications, with an AUC 0.736 (95% CI 0.593–0.880), p = 0.001, and sensitivity 66.7% and specificity 84.6% at a cut-off value ≥ 40.4 pg/mL. Conclusions Low preoperative adiponectin levels are associated with the development of postoperative SIRS, but not postoperative complications, following colorectal cancer surgery.